Literacy, Learning and ‘Participatory Parity’ - Lyn Tett (Adult Education Research Conference, 2014)
This paper investigates if participation in literacy programs contributes to alleviating social injustice using the lens of ‘participatory parity’ (Fraser, 2008). It argues that using this lens enables a focus on how social structures operate to deny social justice to some and so challenges an individual deficit approach to learners.